Impact of oceanic reorganizations on the ocean carbon cycle and atmospheric carbon diocide content - Marchal, Olivier; Stocker, Thomas F.; Joos, Fortunat (Paleoceanography, 1998)
A zonally averaged, circulation-biogeochemical ocean model is used to explore how the distribution of PO4 and δ13C in the major basins and the atmospheric pCO2 respond to rapid changes in the thermohaline circulation (THC). Different evolutions of the Atlantic THC are simulated by applying surface freshwater pulses typical, for example, of Heinrich events and the last deglaciation. In the model, when the THC completely collapses, PO4 increases (>0.5 mmol m−3) and δ13C decreases (<0.5‰) in Atlantic bottom waters because of a drop in ventilation by North Atlantic Deep Water (NADW). Although consistent with the traditional interpretation of sedimentary records of benthic foraminiferal Cd/Ca and δ13C, the relationship between the degree of PO4 enrichment and δ13C depletion and the degree of THC reduction is not linear. In the NADW formation area the preformed PO4 declines (<0.5 mmol m−3) because of an imbalance between biological uptake and PO4 supply from the deep, and the preformed δ13C rises (>1‰) because of a longer residence time of waters at the surface. These surface anomalies are propagated to the bottom North Atlantic when the THC resumes. When the thermohaline overturning is only partly reduced and at shallower depths, changes in bottom waters are accompanied by a PO4 decrease and δ13C increase at intermediate levels in the mid-latitude Atlantic. This results in enhanced vertical gradients of these properties consistent with chemical and isotopic reconstructions for the last glacial maximum. Finally, the atmospheric pCO2 increases during the cold period in the North Atlantic when the THC is reduced with an amplitude (7–30 µatm) and timescale (∼10² to 1–2 × 10³ yr) depending on the intensity of the THC change. This is qualitatively consistent with recent data from an Antarctic ice core documenting a pCO2 increase during the Younger Dryas and after Heinrich events 4 and 5.